Implementasi Data Mining Penjualan Produk Kosmetik Pada PT. Natural Nusantara Menggunakan Algoritma Apriori - Fajar Adhinda Kusuma Wardani; Titin Kristiana (LPPM Universitas Bina Sarana Informatika, 2020)
Women's life can not be separated from cosmetics. In addition to beautifying themselves, cosmetics are also used for health purposes. Cosmetics are basically one of the basic needs of women. Every day the sales transaction data at PT. Natural Nusantara is increasing and causing huge data storage. Most sales transaction data is only used as archives without being used properly. The data should be used to see the relevance of each item purchased by consumers simultaneously. This research analyzes data using a priori algorithm method, with this method it is known that cosmetic products purchased simultaneously and most sold by looking at the value of support and confidence. In the process of data processing using manual calculation and RapidMiner 5.3 software to analyze datasets at PT. Natural Nusantara. The results of this study use 10% support and 50% confidence. This study produced 7 rules for association rules.